Classification of invasive breast carcinoma according to st gallen classification 2011 with emphasis on Ki67 index among sabahan population - Yusof, Muhd Afif Mohd (2016)
Background: Invasive Breast Carcinoma of No Specific Type (IBC NST) is divided into four subtypes using Estrogen Receptor (ER), Progesterone Receptor (PR) and Human Epidermal Receptor 2 (HER2) immunohistochemistry markers. They are classified into Luminal A (LA), Luminal B (LB), HER2 Overexpressed (HO) and Triple Negative (TN) subtype. The St. Gallen 2011 Classification recognizes the use of Ki67 proliferative index to identify LB subtype from LA group. LB has a worse prognosis and different approach of treatment. Objective: This study aimed to identify HER2 negative LB subtype according to St Gallen Classification 2011 using Ki67 and to compare the clinicopathological features of different subtypes. Methods: Tissue biopsies of LA subtype were stained with antibody towards Ki67. LA cases with Ki67 ≥14% were reclassified as LB subtype. Luminal subtypes with corresponding stage (tumour size), histological grade and lymph node metastases were compared. Univariate analysis using simple logistic regression was performed to determine the percentage of Ki67 expression among all IBC NST cases. McNemar’s test was used for paired categorical analysis. All calculations performed using SPSS version 22 and a pvalue of <0.05 was set to denote statistical significance. Results: LA is the most common subtype (43%; 68/158), followed by LB (33%; 52/158). Only 37 out of 68 cases were stained with Ki67 due to sample limitations. From these LA cases, 43% (16/37) showed Ki67 ≥14% (reclassified as LB subtype). There was significant result when using Ki67 (P<0.001; P<0.05). However, LB subtype showed statistically insignificant result when compared with between stage, grade and lymph node status. Conclusion: The classification according to the St Gallen Classification 2011 utilized Ki67 marker in addition to ER, PR and HER2 in identifying luminal B subtype cases, which have a worse prognosis.